Mouse feeding study and microbiome analysis of sourdough bread for evaluation of its health effects - Kwon, Joon-Gi; Park, Sung-Hoon; Kwak, Jeong-Eun; Cho, Jae Hyoung; Kim, Gooyoun; Lee, Deukbuhm; Kim, Dong Hyun; Kim, Hyeun Bum; Lee, Ju-Hoon (Frontiers in Microbiology, 2022)
Sourdough bread fermented with yeast and lactic acid bacteria (LAB) is thought to have various beneficial health effects. To evaluate these effects in vivo, a mouse feeding study and microbiome analysis of white bread containing 40% sourdough (WBS) and yeast-leavened white bread (WB) were performed. Although feed consumption and body weight increased with WBS, the glycemic index was reduced, suggesting a diabetes-lowering effect, probably due to the presence of dietary fiber and short-chain fatty acids (SCFA). In addition, a mineral absorption test showed that WBS increased magnesium absorption owing to phytate degradation during fermentation. Interestingly, WBS decreased total cholesterol and triglycerides, probably due to the dietary fiber and SCFA in LAB. In addition, the ratio of low- and high-density lipoprotein was decreased in WBS, implying potential risk reduction for cardiovascular disease. An immunomodulatory assay of WBS revealed that pro-inflammatory cytokines TNF-α and IL-6 were decreased, suggesting anti-inflammatory activity. Gluten degradation by fermentation and antioxidation activity of menaquinol/ubiquinol by gut microbiota also supported the anti-inflammatory activity of sourdough bread. Furthermore, some beneficial gut bacteria, including Akkermansia, Bifidobacterium, and Lactobacillus, were increased in WBS. In particular, Akkermansia has been associated with anti-inflammatory properties. Consequently, WBS might have beneficial effects on health, including decreased glycemic index and cholesterol, increased mineral availability and absorption, anti-inflammatory properties, and establishment of healthy gut microbiota.